Development of Low Phytate Rice by RNAi Mediated Seed-Specific Silencing of Inositol 1,3,4,5,6-Pentakisphosphate 2-Kinase Gene (IPK1) - Ali, Nusrat (Public Library of Science, 2013)
Phytic acid (InsP(6)) is considered to be the major source of phosphorus and inositol phosphates in most cereal grains. However, InsP(6) is not utilized efficiently by monogastric animals due to lack of phytase enzyme. Furthermore, due to its ability to chelate mineral cations, phytic acid is considered to be an antinutrient that renders these minerals unavailable for absorption. In view of these facts, reducing the phytic acid content in cereal grains is a desired goal for the genetic improvement of several crops. In the present study, we report the RNAi-mediated seed-specific silencing (using the Oleosin18 promoter) of the IPK1 gene, which catalyzes the last step of phytic acid biosynthesis in rice. The presence of the transgene cassette in the resulting transgenic plants was confirmed by molecular analysis, indicating the stable integration of the transgene. The subsequent T(4) transgenic seeds revealed 3.85-fold down-regulation in IPK1 transcripts, which correlated to a significant reduction in phytate levels and a concomitant increase in the amount of inorganic phosphate (Pi). The low-phytate rice seeds also accumulated 1.8-fold more iron in the endosperm due to the decreased phytic acid levels. No negative effects were observed on seed germination or in any of the agronomic traits examined. The results provide evidence that silencing of IPK1 gene can mediate a substantial reduction in seed phytate levels without hampering the growth and development of transgenic rice plants.